Consolidation Attributes and Deformation Response of Soft Clay Reinforced with Vertical Scoria Drains under Road Embankment - Hailemariam Merka Gebretsadik; Damtew Tsige Melese; Adamu Beyene Negesa (Advances in Materials Science and Engineering)
Application of vertical drains in soft clay soils is a common practice widely known to facilitate the consolidation rate. To overcome the adverse impact of a long-lasting consolidation process, highly permeable materials such as sand and crushed aggregates are used as drains. However, limited information exists regarding the applicability of scoria gravel as a vertical drain that no concisely documented information is observed in the literature. This study hence aimed at investigating suitability of scoria as a vertical drain in perpetuating the consolidation process of soft clay under highway embankment. Finite element-based numerical simulation was used to model the drain. The model was carried out by using 3D version of Plaxis software. In order to incorporate the effect of gradual load increment on the consolidation rate, the staged construction approach was employed. Both the square and triangular installation patterns were considered in the model in order to explore the critical effects of the drain installation pattern on the rate of consolidation. The numerical analysis also included varying dimensions of the vertical drain so as to investigate the effects of the dimension parameters of the vertically installed scoria drains. The conducted numerical analysis revealed that the rate of consolidation was considerably accelerated with provision of a group of scoria drains. With increase in the diameter of the drain, the consolidation rate increases, whereas the consolidation rate is inversely related to increase in drain spacing. For the drain installed at a spacing of 2 m, a diameter of 0.4 m, and a length of 8 m any arbitrary settlement magnitude is achieved 25 days earlier than the case without drains. Besides, incorporation of scoria drains lessens the pore pressure developed. The comparative analysis conducted on the effect of drain arrangement revealed that no considerable difference was witnessed in the performance of the square and triangular installation patterns even though the consolidation rate remains slightly faster in the case of the triangular installation pattern.